The boundary paradox in the Bithorax complex. (November 2015) - Kyrchanova, Olga; Mogila, Vladic; Wolle, Daniel; Magbanua, Jose Paolo; White, Robert; Georgiev, Pavel; Schedl, Paul
Abstract: The parasegment-specific expression of the three Drosophila Bithorax complex homeotic genes is orchestrated by nine functionally autonomous regulatory domains. Functional autonomy depends upon special elements called boundaries or insulators that are located between each domain. The boundaries ensure the independent activity of each domain by blocking adventitious interactions with initiators, enhancers and silencers in the neighboring domains. However, this blocking activity poses a regulatory paradox — the Bithorax boundaries are also able to insulate promoters from regulatory interactions with enhancers and silencers and six of the nine Bithorax regulatory domains are separated from their target genes by at least one boundary element. Here we consider several mechanisms that have been suggested for how the Bithorax regulatory domains are able to bypass intervening boundary elements and direct the appropriate parasegment-specific temporal and spatial expression of their target gene. Highlights: Boundary elements ensure the functional autonomy of BX-C regulatory domains. Boundaries function by blocking regulatory interactions. BX-C regulatory domains are separated from their target genes by boundaries. Regulation of target gene transcription requires a bypass mechanism. We discuss several possible mechanisms for boundary bypass.